Factors Affecting COVID-19 Vaccination In Pregnant Women at The Padang Tikar Health Center - Sherly Angellina; Luluk Handayani; Siswanto Pabidang; Bima Suryantara (PT. Anagata Sembagi Education, 2024)
COVID-19 vaccination for pregnant women can prevent the risk of exposure to COVID-19, but there are still concerns for pregnant women regarding the contents, side effects and impact of vaccination. So it has a low impact on pregnant women's acceptance of Covid-19 vaccination. The aim of this research is to analyze the factors that influence pregnant women towards COVID-19 vaccination at the Padang Tikar Community Health Center 2022. The research design used is a mixed method, using an analytical observational approach with a purposive sampling technique, with a quantitative sample of 30 respondents and 5 qualitative informants. Data analysis is univariate, bivariate and multivariate. The research results show that the most dominant variable is attitude with a value of OR = 10.482 (95% CI OR 1.364-80.535) meaning that pregnant women who have a less supportive attitude are more at risk of not getting the Covid-19 vaccination, namely 10.482 times more than pregnant women who have supportive attitude towards Covid-19 vaccination. In conclusion, it is hoped that health workers will educate about Covid-19 vaccination by providing support so as to increase the positive attitude of pregnant women.